Triple Brood Production by Northern Bobwhites - D. Clay Sisson (National Quail Symposium Proceedings, 2017)
Most aspects of northern bobwhite (Colinus virginianus) life history are well understood and well documented, including their ability to ‘‘double brood’’ (defined as the same hen successfully hatching 2 broods during a single nesting season). Less understood are the ability and/or prevalence of ‘‘triple broods’’ in the life history of bobwhites. Occasional citing in the literature of triple brooding is often unclear as to whether reference is being made to the attempt at hatching 3 broods in a season or actually doing so. This confusion stems from the interchanging use of the words brood and clutch. While Webster defines ‘‘clutch’’ as either 1) a nest of eggs, or 2) a brood of chicks; ‘‘brood’’ is clearly defined as a group of birds hatching at one time. A closer look at the referenced studies reveals incidences of ‘‘triple clutching’’ where a single hen incubated three nests in one summer, but no published record of a true triple brood. The strict definition of triple brood should be: the same hen successfully hatching 3 broods in a single nesting season. Our nest data from radio-tagged birds collected in the Albany, GA area suggest that this phenomenon is extremely rare. From 1992-2016 we radio-tagged and monitored 2,607 hens during the nesting season on our primary study area in Baker County, GA. These birds produced 1,463 incubated nests and hatched 768 broods. Double broods were fairly common (n = 91) and occurred in all but two of the 25 nesting seasons. Only one incidence of true triple brooding has been documented on this study area during this time period. Adult mortality, nest loss, and the limited duration of the nesting season all work against this level of production. While an interesting aspect of the bird’s natural history, the extremely low rate of occurrence makes it insignificant from a population standpoint.
Keywords: colinus virginianus; northern bobwhite; double broods; Georgia; triple broods